Bargaining at divorce: The allocation of custody - Christine Atteneder; Martin Halla (Johannes Kepler University of Linz, Department of Economics, 2006)
We model the bargaining process of parents over custody at the time of divorce. First we assume an institutional setting where only sole custody is available. In a second step we reform this institutional setting and introduce the possibility of joint custody. We show that some parents, who would not be able to find an agreement in a sole custody regime, can find an agreement after the joint custody reform. Accordingly, our empirical analysis shows that the introduction of joint custody enables more parents to divorce by mutual consent.
Keywords: J12; J13; K36; D1; C78; 330; (joint) custody; divorce; family law; bargaining; Ehe; Familienrecht; Kinderbetreuung; Verhandlungstheorie; Theorie